MENUMBUHKAN KEBERANIAN UNTUK MEMULAI BERWIRAUSAHA BAGI PESERTA PELATIHAN di LKP BELLA SKILL CENTER - Indriyatni, Lies; Wahyuningsih, Susanti; Yuliati, Yuliati (Fokus ABDIMAS, 2022)
This community service is carried out with the aim of opening the insight of LKP BELLA SKILL CENTER participants so that they can become successful entrepreneurs, foster creativity and independence as well as solutions on how to manage capital properly and correctly, in accordance with existing management science rules. The methods used are counseling/lectures and training/workshops as well as assistance in starting a business.From the results of community service carried out at LKP BELLA SKILL CENTER... an illustration is obtained that some of these participants still do not have the courage to become entrepreneurs, lack motivation to be creative and still do not understand the management of their capital correctly, which often results in fear of capital problems.The conclusions that can be drawn are the importance of providing training on tips to become successful entrepreneurs, providing motivation and knowledge about managing capital for participants, which is expected to be able to foster interest and courage in starting a business to achieve success in entrepreneurship as expected, and as far as possible avoiding them. from the risk of capital difficulties and the risk of being ensnared by the practices of moneylenders.Keywords: Entrepreneurship tips, creativity and venture capital